1999
DOI: 10.1002/(sici)1097-0215(19991022)84:5<533::aid-ijc16>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of the AP-1 family in breast cancer: Association of fosB expression with a well-differentiated, receptor-positive tumor phenotype

Abstract: In the present study, the expression of members of the AP‐1 family of transcription factors in breast tumors (n = 53) was investigated by Western blot with antibodies specific for each of the AP‐1 family members (c‐jun, junB, junD and c‐fos, fosB, fra1 and fra2). The tumors were characterized with regard to grading, staging, histology, steroid‐receptor‐expression status and c‐erbB2/neu expression. For comparison, normal breast‐tissue samples, human breast‐cancer cell lines (T47D and MDA‐MB231) and the transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 20 publications
9
79
1
1
Order By: Relevance
“…Kim and colleagues 30 detected under-expression of FosB in pancreatic cancer tissues with lymph node metastasis compared to pancreatic cancer tissues without lymph node metastasis and showed that decreased expression of FosB is associated with reduced survival. In contrast, other studies showed a bipolar FosB expression pattern in breast cancer, 31 whereas our study indicated high FosB expression in melanoma cell lines compared to NHEMs. Moreover, the gene product of NFATC2 was found to be functionally important in malignant melanoma, as it inhibits apoptosis.…”
Section: Genecontrasting
confidence: 99%
“…Kim and colleagues 30 detected under-expression of FosB in pancreatic cancer tissues with lymph node metastasis compared to pancreatic cancer tissues without lymph node metastasis and showed that decreased expression of FosB is associated with reduced survival. In contrast, other studies showed a bipolar FosB expression pattern in breast cancer, 31 whereas our study indicated high FosB expression in melanoma cell lines compared to NHEMs. Moreover, the gene product of NFATC2 was found to be functionally important in malignant melanoma, as it inhibits apoptosis.…”
Section: Genecontrasting
confidence: 99%
“…Proteins were lysed in ice-cold sample buffer (50 mM Tris pH 6.8, 1% sodium dodecyl sulphate (SDS), 10% sucrose and 10 ml ml À1 protease inhibitor cocktail (Sigma, Taufkirchen, Germany)), and protein concentration was determined following the standard protocols and using bovine serum albumin protein standards as described previously (Bamberger et al, 1999;Milde-Langosch et al, 2005).…”
Section: Protein Extractionmentioning
confidence: 99%
“…Band intensities were quantified by densitometry (GS-700 Imaging Densitometer, BioRad, Munich, Germany). Intensities of the specific protein bands were calculated as percent intensity of the control sample and corrected for equal actin loading as previously described (Bamberger et al, 1999).…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Der Proteingehalt im Überstand wurde mit einem "Bicinchoninic-acid"-(BCA-)Protein-Assay ermittelt. WesternBlot-Analysen wurden, wie beschrieben [7], unter Verwendung von 20 μg Protein/Spur in einem 8%igen Polyacrylamidgel durchgeführt. Die Proteine wurden auf eine PVDF-Membran (Immobilon P, Millipore, Eschborn) übertragen und für 1 h mit dem NCL-CD166-Antikörper in einer Verdünnung 1:400 inkubiert.…”
Section: Immunhistochemie Und Western-blot-analysenunclassified